2016
DOI: 10.1016/j.bbalip.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The hyaluronic acid inhibitor 4-methylumbelliferone is an NSMase2 activator—role of Ceramide in MU anti-tumor activity

Abstract: Increased synthesis of hyaluronic acid (HA) is often associated with increased metastatic potential and invasivity of tumor cells. 4-Methylumbelliferone (MU) is an inhibitor of HA synthesis, and has been studied as a potential anti-tumor drug to inhibit the growth of primary tumors and distant metastasis of tumor cells. Although several studies reported that the anticancer effects of MU are mediated by inhibition of HA signaling, the mechanism still needs to be clarified. In a previous study we demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
(105 reference statements)
1
8
1
Order By: Relevance
“…While previous studies found that SMPD3 overexpression was sufficient to slow the proliferation rate of various cancer cell lines, including the breast cancer line MCF-7, the osteosarcoma line F4328, and the hepatocellular carcinoma line JHH-7, we found no effect on proliferation of either oral dysplasia or OSCC cell lines [20,21,27]. However, our data suggest that SMPD3 does inhibit the capacity of cells for migration and invasion, in agreement with previous studies [30].…”
Section: Discussionsupporting
confidence: 91%
“…While previous studies found that SMPD3 overexpression was sufficient to slow the proliferation rate of various cancer cell lines, including the breast cancer line MCF-7, the osteosarcoma line F4328, and the hepatocellular carcinoma line JHH-7, we found no effect on proliferation of either oral dysplasia or OSCC cell lines [20,21,27]. However, our data suggest that SMPD3 does inhibit the capacity of cells for migration and invasion, in agreement with previous studies [30].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, suppression of exosomal PD-L1 may be a promising personalized therapy. It has been reported that GW4869 could decrease the secretion of tumor cell exosome, which inhibit the cell growth [51]. Although we can not observe the signi cantly inhibiting effect of GW4869 on the osteosarcoma cell growth in vitro in the present study, inhibition of exosome secretion by GW4869 could suppress the pulmonary metastasis in vivo study.…”
Section: Discussioncontrasting
confidence: 72%
“…We chose SMases knockdown to demonstrate the utility of the QD approach because they are enzymes activated in the CNS following various kinds of stress (Qin et al . , , ; Qin and Dawson ). Knockdown efficiency by QD‐siRNA was roughly comparable to a commercially siRNA delivery lipofection kit but without the cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, siRNA was delivered in sufficient quantities as to effect a substantial change in enzyme expression as shown by luciferase and sphingomyelinase assay. We chose SMases knockdown to demonstrate the utility of the QD approach because they are enzymes activated in the CNS following various kinds of stress (Qin et al 2009(Qin et al , 2015. Knockdown efficiency by QD-siRNA was roughly comparable to a commercially siRNA delivery lipofection kit but without the cytotoxicity.…”
Section: Fig 6 Expression Of Luciferase In Hct Cellsmentioning
confidence: 99%